Income and Views on Minimum Living Standards - David W. Johnston; Nidhiya Menon (Institute of Labor Economics (IZA), 2021)
This paper explores the association between income and stated views on minimum living standards; that is, views on items and activities that no one in today's society should have to go without. Using data from a large nationally representative survey, we find the rich are less empathetic. In our baseline model, people at the bottom of the income distribution report 10% more items as essential than do people at the top of the income distribution. The negative relationship between income and recommended minimum living standards is robust to conditioning on a large covariate set, and remains evident when we use alternative measures of economic status, such as wealth and neighborhood advantage. We find that area-level income inequality amplifies the negative income gradient, and that the rich are no more empathetic towards children than they are towards adults. We also find that changes in people's views across time are relatively small, and unrelated to major economic life events. An explanation for this stability is that views are formed primarily in childhood. We find that economic status in childhood has strong effects on views during adulthood, but that intergenerational economic mobility is unimportant.
Keywords: D31; D63; D64; H24; H31; 330; income; empathy; living standards; inequality; childhood shocks; culture